2012
DOI: 10.1111/j.1526-4637.2012.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Epidural Depth: Correlation Between Needle Angle, Cervical Anatomy, and Body Surface Area

Abstract: Objectives Prior to performing a cervical interlaminar epidural steroid injection (CIESI), knowledge of the depth from lamina to epidural space may assist in preventing cord injury. Methods This is a prospective analysis of data including gender, age, weight, height, previous surgery, neck circumference, distances from tip of chin to sternal notch, occiput to C7 vertebral prominence, and ear lobe to tip of shoulder, pain score, angle from C7 vertebral prominence to the back, depth at which the Tuohy needle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the cervical region, anatomical studies have shown not only high rate of discontinuity, but also anatomic variability in the ligamentum flavum, which plays an inevitable role in the LOR technique. This morphological variability is associated with a higher false-positive rate during CIESI procedures [ 7 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the cervical region, anatomical studies have shown not only high rate of discontinuity, but also anatomic variability in the ligamentum flavum, which plays an inevitable role in the LOR technique. This morphological variability is associated with a higher false-positive rate during CIESI procedures [ 7 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cervical epidural space is anatomically relatively small compared with the thoracic or lumbar regions and approximates the brain components 4. Incorrect needle advancement and drug injections can lead to catastrophic complications 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been suggested that TF ESI is more effective than IL ESI because the TF approach has the advantage of being able to place drugs directly to the site of pathology by targeting the posterior side of the intervertebral foramen, whereas in the IL approach, ventral epidural spread was found in only 28% of cases (26). However, in other studies, the cervical region has a narrower epidural space than the lumbar spine (27), and thus the drug spreads well to the ventral epidural space, which is mainly the site of the lesion. Therefore the factor that the drug spreads to the anterior epidural space is strongly related to the dose of the drug (28).…”
Section: Discussionmentioning
confidence: 89%